Strategi Bisnis Dalam Mengembangkan Trend Hijab di Kalangan Remaja - Hasibuan, Nurlaila; Batubara, Chuzaimah (LPPM Universitas Labuhanbatu, 2023)
The hijab trend among teenagers has experienced significant developments in recent years. More and more young girls are choosing to wear the hijab as part of their identity and lifestyle. This phenomenon provides a great opportunity for business people in the hijab industry to develop effective business strategies to meet increasing market demand. This abstract aims to analyze business strategies that can be used to develop hijab trends among teenagers. First, identifying youth trends and preferences regarding hijab is an important first step. Furthermore, strong brand development becomes one of the important strategies in creating attractiveness for teenagers. Brands that have values that are in line with the aspirations and values of young people will be more successful in attracting their attention. Product innovation is also a key factor in expanding the hijab trend among teenagers. Business people need to continue to develop hijab products by paying attention to creative designs, functionality and comfort of use.